Pengaruh Kemampuan Manajerial Kepala Madrasah dan Organizational Citizenship Behavior Terhadap Kinerja Guru - Wilda Oktaviani Untung; Zulqarnain Zulqarnain; Sukarno Sukarno (Journal of Educational Research, 2022)
This study aims to determine the effect of the managerial ability of the madrasah principal and organizational citizenship behavior on teacher performance. This research uses a research design with a quantitative approach. Data analysis using multiple regression test, hypothesis testing with simultaneous and partial methods and correlation test with the coefficient of determination. The results of this research explain that managerial ability and organizational citizenship behavior have a positive and significant effect on teacher performance. The findings of this study confirm managerial ability and organizational citizenship behavior for schools is to improve the quality of teacher performance. Furthermore, the existence of a strong managerial ability at the head of the madrasa, causes teacher performance to run optimally. Penelitian ini bertujuan untuk mengetahui pengaruh kemampuan manajerial kepala madrasah dan organizational citizenship behavior terhadap kinerja guru. Riset ini menggunakan rancang penelitian dengan pendekatan kuantitatif. Analisis data menggunakan uji regresi berganda, pengujian hipotesis dengan metode simultan dan parsial serta uji korelasi dengan koefisien determinasi. Hasil dari riset ini menjelaskan kemampuan manajerial dan organizational citizenship behavior berpengaruh positif dan signifikan terhadap kinerja guru. Temuan penelitian ini mengkonfirmasi kemampuan manajerial dan organizational citizenship behavior bagi sekolah adalah untuk meningkatkan kualitas kinerja guru. Lebih lanjut, adanya kemampuan manajerial yang kuat pada kepala madrasah, menyebabkan kinerja guru dapat berjalan dengan optimal.